Trusting God’s Redemption On Psalm 130: A Literary-Structure Approached - Philip Suciadi Chia; Juanda Juanda (Theological Journal Kerugma, 2022)
The pressures of life that cause suffering are real things in life. The same thing happened to the psalmist recorded in Psalm 130:1-8. There are two big possibilities when someone faces a problem, they will move away from God or draw closer to God. In the narrative of Psalm 130:1-8, the psalmist draws closer to God. When the psalmist trusting God’s redemption generates the attitude to wait upon the Lord. Although God has not heard my prayer yet, I want to trust the Lord that he will deliver me despite I do not know when he will release me. I want to live in trust to the Lord because I believe that my faith will help me to endure in my problems, to still wait upon the Lord. I want to remember his characters so that I do not want to lose my faith in the midst of my suffering. This Psalm is begun with petition to the Lord and it is ended up by describing God’s characteristic.